Synthesis and characterization of Ni–P coated hexagonal boron nitride by electroless nickel deposition - Maleque, Md. Abdul (Allerton Press, 2015)
Electroless plating has been receiving a steady progress over the last decade on the modification of the surface properties of ceramic materials in order to produce composite coatings with unique characteristics for critical tribological systems. In this work, an electroless nickel deposition process was used to deposit nickel-phosphorous (Ni–P) coating on hexagonal boron nitride (h-BN) particles via hypophosphite- reduced acid bath solution. The substrate particles were initially subjected to series of pre-treatment opera- tion in order to ensure that the particles are cleaned and catalytically active prior to electroless plating. The characterization of the as-received and Ni-coated powder was studied through scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy and field emission scanning electron microscopy (FESEM). The result reveals that the pretreatment of h-BN powder provides substrate particle surfaces with coarse and roughened structures which are normally considered suitable for Ni–P deposition. Moreover, the result of the EDX analysis confirms the existence of nucleating agents and Ni–P coating on the surface of the treated h-BN powder. The cross-sectional microstructure of the coated powder shows that the h-BN particles were embedded in a continuous matrix layer of Ni–P deposit. The EDX mapping profiles further indicate that the deposited Ni–P alloy mass was uniformly distributed on the surface of the Ni–P codeposited h-BN particles (Ni–P–h-BN). The successful development of Ni coated h-BN powder will raise the potential of h-BN as a high-performance coating material.